(untitled) (ENTHYMEMA, 2020)
This paper aims to interpret the peculiar form of novel elaborated by Elsa Morante throughout the european literary scenario of the XXth century. Spanning her statements on poetics gathered in Pro o contro la bomba atomica and setting the analysis on her debut novel, Menzogna e sortilegio (1948), the purpose is to highlight the structuring function of the plot in her works, as a tension aimed to master the time logic of reality and as will to communicate with the reader. Such a realistic heritage - following the definition of realism given by G. Lukács - has been observed in its interweaving with typical forms of popular fiction and in its dialectic relation with the modernist characteristics of Morante’s style.